Reconstruction of ancient Russian text - Basangova, Tamara G. (The New Research of Tuva, 2014)
Review to: Olyadykova L.V., Burykin A.A. The Tale of Igor's Campaign (Slovo o polku Igoreve). Contemporary problems of philological analysis. Studies and articles. Reconstruction of ancient Russian text, translation, comments / Publishing editor S.A. Myznikov. Elista: Kalmyk State University Publishing, 2012. 267 P.
Keywords: edition-2014; review; history; Ancient Russia; lay; Philology